1997
DOI: 10.1038/bjc.1997.399
|View full text |Cite
|
Sign up to set email alerts
|

Leukaemia and non-Hodgkin's lymphoma in children and young adults: are prenatal and neonatal factors important determinants of disease?

Abstract: Summary A medical record-based study of leukaemia and non-Hodgkin's lymphoma diagnosed before the age of 30 years was carried out at three hospitals in the south of England. Findings for 177 cases and 354 age-and sex-matched controls are presented here. For documented viral infection in pregnancy, the odds ratio (OR) was 6.0 [95% confidence interval (Cl) 1.2-29.7] for leukaemia and infinity (95% Cl 1.2-) for non-Hodgkin's lymphoma. Mothers of leukaemic cases were more likely to be anaemic, the OR for a pregnan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
98
4
2

Year Published

2000
2000
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(114 citation statements)
references
References 52 publications
10
98
4
2
Order By: Relevance
“…20 Our findings for lymphatic cancers are similar to those found in children, e.g., for acute myeloid leukemia. 21 Women who were small at birth were at an increased risk of endometrial cancer in this study. Without any directly comparable studies with independent consistent results, there remains the possibility that this may be a chance finding.…”
Section: Comparisons With Other Studiesmentioning
confidence: 50%
“…20 Our findings for lymphatic cancers are similar to those found in children, e.g., for acute myeloid leukemia. 21 Women who were small at birth were at an increased risk of endometrial cancer in this study. Without any directly comparable studies with independent consistent results, there remains the possibility that this may be a chance finding.…”
Section: Comparisons With Other Studiesmentioning
confidence: 50%
“…vitamin K is not new -concerns having been expressed about the proven association between Synkavit (vitamin K 2 ) and kernicterus, documented cases of babies given oxytocics intended for the mother, and the use of unlicensed oral preparations. Indeed, even before the childhood cancer controversy such debate -enhanced by the growth of the natural childbirth movement -had resulted in marked variations between the policies of individual clinicians Epidemiology Table 5 Centre specific odds ratios (OR) and 95% confidence intervals (CI) for intramuscular vitamin K, unadjusted and adjusted for mode of delivery, admission to special care baby unit and low birth weight Ansell et al, 1996;Roman et al, 1997;4 Passmore et al, 1998a;5 McKinney et al, 1998;6 Parker et al, 1998.…”
Section: Discussionmentioning
confidence: 99%
“…vitamin K prophylaxis became a controversial topic when Golding et al (1992) reported that children who received it by this route were almost three times as likely to develop leukaemia as children who received it orally or not at all. Although subsequent studies failed to confirm these findings (Ekelund et al, 1993;Klebanoff et al, 1993;Olsen et al, 1994;Ansell et al, 1996;von Kries et al, 1996;Roman et al, 1997;McKinney et al, 1998;Parker et al, 1998;Passmore et al, 1998a,b), inconsistencies in their results have left lingering doubts about the safety of I.M. administration (Kaufman, 1999).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This possible association has been studied for melanoma (Andersson et al, 2001;McCormack et al, 2005;Ahlgren et al, 2007) and other types of cancer (Le Marchand et al, 1988;Tibblin et al, 1995;Roman et al, 1997;Wanderås et al, 1998;Vatten et al, 2002;Hjalgrim et al, 2004;Nilsen et al, 2005;Michos et al, 2007). The results are inconclusive; however, there seems to be an association between birth weight and the risk for some cancer forms.…”
mentioning
confidence: 99%